ANALISIS SUPPLY CHAIN MANAGEMENT BERBASIS SCOR PADA AGROINDUSTRI JUS SARI MENGKUDU DI KABUPATEN JEMBER - R.Abdoel Djamali; Naning Retnowati; Danang Eka Putra; Deltaningtyas Tri Cahyaningrum (Journal of Innovation Research and Knowledge, 2026)
Noni juice agroindustry is one of the bio-pharmaceutical businesses that has significant potential in developing herbal health beverage products in Jember Regency. However, the implementation of supply chain management in this agroindustry still faces several challenges, including unstable raw material supply, inconsistent raw material quality, limited production technology, weak information integration, and suboptimal distribution and marketing systems. This study aimed to: (1) analyze the supply chain structure of the noni juice agroindustry in Jember Regency; (2) analyze supply chain management performance based on the Supply Chain Operations Reference (SCOR) model; (3) identify constraints in supply chain management implementation; and (4) formulate supply chain development strategies for the noni juice agroindustry. The research employed a descriptive method using a mixed-method approach combining quantitative and qualitative analysis. The analysis was conducted using the SCOR model consisting of plan, source, make, deliver, and return. The results showed that the supply chain of the noni juice agroindustry involves farmers, collectors, agroindustry processors, distributors, and final consumers. Based on the SCOR performance measurement, the supply chain performance obtained an average score of 3.12, which falls into the moderate category. The source and deliver stages became the main critical points due to unstable raw material continuity, inconsistent product quality, and suboptimal distribution systems. Development strategies that can be implemented include strengthening farmer partnerships, digitalizing supply chain systems, modernizing production technology, implementing GMP and HACCP standards, and strengthening digital-based marketing to improve supply chain efficiency and the competitiveness of the noni juice agroindustry in Jember Regency.